Proposed economic strategy for the OECS/ECCB area (Eastern Caribbean Central Bank BasseterreKN, 1993)
With the advent of large trading blocs and global liberalization, it behoves the OECS to develop a short term contingency plan to rescue the economies should the worse case scenario with respect to the banana industry come to pass; stresses the importance of implementing a medium to long-term strategy for transforming the economies and making them more self-dependent and internationally competitive. To this end an economic development strategy is proposed. This paper therefore looks at the natural resource base of the region; the agricultural manufacturing and services sectors; and the institutional framework. Specific projects which can be undertaken are suggested and constraints to the strategy are identified.
DC